2023
DOI: 10.1093/ofid/ofad106
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Plaque Composition and Severity Relate to the Inflammasome in People With Treated Human Immunodeficiency Virus

Abstract: Inflammasome activation is increased in people with HIV (PWH), but its relationship with coronary plaque is poorly understood in this setting. In a large HIV cardiovascular prevention cohort, relationships between caspase-1, IL-1β, and IL-18 and coronary plaque indices were assessed by multivariate logistic regression. Higher IL-18 and IL-1β were associated with Leaman score, an integrative measure of plaque burden and composition. As Leaman score >5 is associated with cardiovascular events in the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In PWH on ART and presenting a low-to-moderate traditional atherosclerotic cardiovascular disease (ASCVD) risk, but with an abundance of plaque, elevated levels of IL-18 and IL-1β were found to be connected to the Leaman score. The Leaman score serves as an indicator of atherosclerotic burden, which is associated with cardiovascular events in the general population [1,13]. The same study found a correlation between the NLRP3 inflammasome and coronary artery plaque composition and severity in PWH on ART.…”
Section: Introductionmentioning
confidence: 79%
“…In PWH on ART and presenting a low-to-moderate traditional atherosclerotic cardiovascular disease (ASCVD) risk, but with an abundance of plaque, elevated levels of IL-18 and IL-1β were found to be connected to the Leaman score. The Leaman score serves as an indicator of atherosclerotic burden, which is associated with cardiovascular events in the general population [1,13]. The same study found a correlation between the NLRP3 inflammasome and coronary artery plaque composition and severity in PWH on ART.…”
Section: Introductionmentioning
confidence: 79%